Compendium of neotropical termite genera: morphology and ecology database, ontology and applicability - Guimarães, Marco Paulo Macedo (2022)
Biological databases are fundamental tools for modern research, offering a wide range of relevant data. Over the past two decades, the explosion of interconnected data has spurred the development and adoption of database technologies. Here we propose the ﬁrst termite morphology and ecology database model, coupled with a standard ontology, and apply the database in a speciﬁc study. With the database, it was possible to extract information about the internal and external morphology and ecology of the 108 genera that occur in the Neotropical region. We also created an ontology model based on the internal and external morphology of termites to support the integration between databases. Furthermore, we show that it is possible to apply the database to extract information that can be used in a speciﬁc study. Keywords: Isoptera. Catalogue. Graph. Entomology.